Leaf day respiration: low CO2 flux but high significance for metabolism and carbon balance. Issue 4 (2nd October 2017) - Tcherkez, Guillaume; Gauthier, Paul; Buckley, Thomas N.; Busch, Florian A.; Barbour, Margaret M.; Bruhn, Dan; Heskel, Mary A.; Gong, Xiao Ying; Crous, Kristine Y.; Griffin, Kevin; Way, Danielle; Turnbull, Matthew; et al.
Summary: It has been 75 yr since leaf respiratory metabolism in the light (day respiration) was identified as a low‐flux metabolic pathway that accompanies photosynthesis. In principle, it provides carbon backbones for nitrogen assimilation and evolves CO2 and thus impacts on plant carbon and nitrogen balances. However, for a long time, uncertainties have remained as to whether techniques used to measure day respiratory efflux were valid and whether day respiration responded to environmental gaseous conditions. In the past few years, significant advances have been made using carbon isotopes, 'omics' analyses and surveys of respiration rates in mesocosms or ecosystems. There is substantial evidence that day respiration should be viewed as a highly dynamic metabolic pathway that interacts with photosynthesis and photorespiration and responds to atmospheric CO2 mole fraction. The view of leaf day respiration as a constant and/or negligible parameter of net carbon exchange is now outdated and it should now be regarded as a central actor of plant carbon‐use efficiency. Contents Summary 986 I. Introduction 987 II. Pioneering metabolic studies of day respiration with 14 C 987 III. Metabolic flux pattern of day respiration 988 IV. Significance of day respiration for leaf N assimilation 991 V. Significance of day respiration for leaf gas exchange 992 VI. Is day respiration influenced by CO2 mole fraction? 995 VII. Significance of day respiration at the plant and ecosystem levels 997 VIII. Conclusions and perspectives 998 References 998